Efavirenz exposure, alone and in combination with known drugs of abuse, engenders addictive-like bio-behavioural changes in rats - Marisa Möller (Nature Portfolio, 2018)
Abstract Efavirenz is abused in a cannabis-containing mixture known as Nyaope. The addictive-like effects of efavirenz (5, 10 and 20 mg/kg) was explored using conditioned place preference (CPP) in rats following sub-acute exposure vs. methamphetamine (MA; 1 mg/kg) and Δ9-tetrahydrocannabinol (THC; 0.75 mg/kg). The most addictive dose of efavirenz was then compared to THC alone and THC plus efavirenz following sub-chronic exposure using multiple behavioural measures, viz. CPP, sucrose preference test (SPT) and locomotor activity. Peripheral superoxide dismutase (SOD), regional brain lipid peroxidation and monoamines were also determined. Sub-acute efavirenz (5 mg/kg) had a significant rewarding effect in the CPP comparable to MA and THC. Sub-chronic efavirenz (5 mg/kg) and THC + efavirenz were equally rewarding using CPP, with increased cortico-striatal dopamine (DA), and increased lipid peroxidation and SOD. Sub-chronic THC did not produce CPP but significantly increased SOD and decreased hippocampal DA. Sub-chronic THC + efavirenz was hedonic in the SPT and superior to THC alone regarding cortico-striatal lipid peroxidation and sucrose preference. THC + efavirenz increased cortico-striatal DA and decreased serotonin (5-HT). Concluding, efavirenz has dose-dependent rewarding effects, increases oxidative stress and alters regional brain monoamines. Efavirenz is hedonic when combined with THC, highlighting its abuse potential when combined with THC.